Time, timing, and conflicting temporalities in experimental urban mobility governance - Franziska X. Meinherz (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
In this article, I explore the role of experiments in urban mobility governance. I ask to what extent they are responses to the challenges of coexisting timeframes and temporalities and what challenges the latter pose for experiments. My analysis is based on field visits and interviews with urban administrations and public transport providers in Copenhagen, Lisbon, and Madrid. My results show that urban administrations use experimentation as a form of reflexive, transformative governance. Public transport providers use experiments to navigate tensions between rapid regulatory changes and technological innovation and their long-lived infrastructure. Both actor groups stressed the importance of disruptions as natural experiments. Urban administrations used disruptions for experimentation to fast-track approved but difficult-to-implement projects. The temporary nature of experiments can pose a risk: It makes them vulnerable to political attacks. To mitigate backlash, good timing is critical.